Investigation in ability to improving accuracy of interpolation method for height anomalies using terrain data and remove-restore technique - Hoa, Pham Thi (Vietnam Journal of Earth Sciences, 2015)
This article presents theory and experience in improving accuracy of interpolation for height anomaly using terrain data and remove-restore technique. Height anomaly is distance from the quasigeoid to the ellipsoid surface. It is a characteristic of gravitational potential and very important information in geodesy and the other branches of earth science. There are different methods of determining height anomaly as: gravitation, gravitation - geodesy, GPS and leveling...ect. In addition to, it can be determining by interpolating with data of exist points. In order to improving accuracy of interpolation, it should be used terrain data and remove - restore technique. Remove -restore technique has been popular in physical geodesy so many scientists in almost of countries have used for a long time. Theoretical basic of improving accuracy of interpolation using terrain data and remove -restore technique is division of height anomaly into two parts. The first one is long wave being smooth and varying regularly. The other one is short wave (terrain effect in height anomaly) being rough and varying complicatedly. Results of interpolating will be more accurate if short wave is removed in order to interpolating the remain long wave and then restored short wave for results of interpolating. According to this theory, numerical investigations are done within four areas of Viet nam. The data used are GPS-TC anomalies and terrain elevation. The anomalies are interpolated in both cases: normal interpolation and interpolation using terrain data and remove - restore technique. In both cases, some points in set points having height anomalies are chosen being origin in order to interpolating for the other points. Then, results of interpolation are compared with exist values in order to predicting theirs accuracy. Numerical results indicate that if average distance between points approximately 20 km, using terrain data and remove - restore technique can increase accuracy of height anomaly interpolation from 50% to 80% and average is 64%. This increase is very remarkable. Results of this study have important implications, contributing to saving time and costs for determining height anomalies. References Phạm Thị Hoa, 2012: Luận án tiến sỹ kỹ thuật “Nghiên cứu xác định ảnh hưởng của độ cao địa hình trong dị thường độ cao và độ lệch dây dọi ở Việt nam”. Trường Đại học Mỏ Địa chất. Shaofeng Bian, 1996: Topography supported GPS levelling. Zeitschrift fur Vermessungswesen, 121, Jahrgang 1996. Verlag Konrad Wittwerk GmbH Stuttgart, Germany, S.109-113. Tom Lyche and Knut Morken, 2008: “Spline Methods”, Department of Informatics, Centre of Mathematics for Applications, University of Oslo.